Mood Disorders in Young People With Acquired Brain Injury: An Integrated Model - Roberts, Henrietta; Ford, Tamsin J.; Karl, Anke; Reynolds, Shirley; Limond, Jenny; Adlam, Anna-Lynne R. (Frontiers in Human Neuroscience, 2022)
Purpose/Objective: Young people with paediatric acquired brain injury (pABI) are twice as likely to develop a mood disorder as their peers, frequently have significant unmet socio-emotional needs, and are at over double the risk of going on to use adult mental health services. Recent years have seen significant advances in the development of interventions for young people with mood disorders. However, evidence-based approaches to mood disorders in pABI are lacking and surprisingly little work has evaluated clinical and neuro-developmental models of mood disorders in this population. Method: We review the literature regarding key mechanisms hypothesised to account for the increased vulnerability to mood disorders in pABI: First we summarise the direct neurocognitive consequences of pABI, considering the key areas of the brain implicated in vulnerability to mood disorders within a neurodevelopmental framework. Second, we outline five key factors that contribute to the heightened prevalence of mood disorders in young people following ABI. Finally, we synthesise these, integrating neuro-cognitive, developmental and systemic factors to guide clinical formulation. Results and implications: We present a framework that synthesises the key mechanisms identified in our review, namely the direct effects of pABI, neurocognitive and neuroendocrine factors implicated in mood and anxiety disorders, maladaptive neuroplasticity and trauma, structural and systemic factors, and psychological adjustment and developmental context. This framework is the first attempt to provide integrated guidance on the multiple factors that contribute to elevated life-long risk of mood disorders following pABI.